Tuan Guru's communication strategy in resolving religious ideological conflict in Lombok, Indonesia - Pardi, Muh. Habib Husnial (Jurnal Ilmu Dakwah, 2024)
Purpose – This article attempts to explain Tuan Guru's communication strategy in conflict resolution between Islamic groups in Lombok, namely between communities affiliated with the Nahdlatul Wathan organization versus the Sunnah (Wahhabi) group.Method – This article uses a qualitative method-case study. Data were collected through observation, documentation, and interviews and then analyzed through the stages of condensation, display, interpretation, and conclusion.Result  – The results of this study show that the source of conflict that occurs in the community is the difference in religious ideology between Aswaja Islam and Wahhabi Islam. Second, the master teacher was able to mediate the conflict by using religious and cultural communication strategies. He campaigned for peace values derived from Islamic teachings and strengthened socio-cultural capital as a tool for harmony, such as silaturrahim in the tradition of begawe (feast) of marriage, birth, and death.Implication – This article contributes to the study of Tuan Guru employs a communication strategy that emphasizes dialogue and mutual understanding, facilitating open discussions to bridge gaps between differing religious ideologies. By fostering a respectful exchange of perspectives, he creates a platform for resolving conflicts and promoting religious harmony.Originality/Value – This research exploration of tuan guru not only as a leader of the pesantren but also as a "peacemaker" This shows that the guru's leadership is quite strategic in terms of conflict and peace.***Tujuan - Artikel ini bertujuan menjelaskan strategi komunikasi Tuan Guru dalam penyelesaian konflik antara kelompok-kelompok Islam di Lombok, yaitu antara komunitas yang terafiliasi dengan organisasi Nahdlatul Wathan versus kelompok Sunnah (Wahabi). Metode - Artikel ini menggunakan metode kualitatif-studi kasus. Data dikumpulkan melalui observasi, dokumentasi, dan wawancara kemudian dianalisis melalui tahapan kondensasi, tampilan, interpretasi, dan kesimpulan. Hasil - Hasil dari studi ini menunjukkan bahwa sumber konflik yang terjadi dalam masyarakat adalah perbedaan ideologi agama antara Islam Aswaja dan Islam Wahabi. Kedua, guru besar mampu memediasi konflik dengan menggunakan strategi komunikasi agama dan budaya. Dia melakukan kampanye untuk nilai-nilai perdamaian yang bersumber dari ajaran Islam dan memperkuat modal sosial-budaya sebagai alat untuk keharmonisan, seperti silaturrahim dalam tradisi begawe (persilatan) pernikahan, kelahiran, dan kematian. Implikasi - Artikel ini memberikan kontribusi pada studi tentang Tuan Guru yang menggunakan strategi komunikasi yang menekankan dialog dan pemahaman saling, memfasilitasi diskusi terbuka untuk menjembatani kesenjangan antara ideologi agama yang berbeda. Dengan mendorong pertukaran pandangan yang saling menghormati, dia menciptakan platform untuk penyelesaian konflik dan mempromosikan harmoni agama. Orisinalitas/Nilai - Penelitian ini mengeksplorasi Tuan Guru bukan hanya sebagai pemimpin pesantren tetapi juga sebagai "peacemaker." Hal ini menunjukkan bahwa kepemimpinan guru cukup strategis dalam hal konflik dan perdamaian.